EFFECT OF POULTRY DROPPINGS ON DIESEL CONTAMINATED SOIL AND EVALUATING ITS PHYSICOCHEMICAL PROPERTIES - K.SATHEES KUMAR,; RAJESHWARI SIVARAJ,; A.RADHAKRISHNA, (International Journal of Pharma and Bio Sciences, 2015)
This work was designed to determine the effect of poultry droppings on diesel contaminated soil and evaluate its physiochemical properties. In this study, different ratios of diesel contaminated soil and poultry droppings have been used as raw materials. The mixture of diesel contaminated soil and poultry droppings were allowed to composting process for 40 days. The physicochemical parameters like pH, EC, organic carbon, organic matter, total nitrogen, total phosphorous, total potassium, enzymes level (alkaline phosphatase(ALP), acid phosphatase (ACP), dehydrogenase and urease) and microbial population were analysed at 0, 10, 20, 30 and 40 days intervals of poultry droppings treated diesel contaminated soil. The changes created by poultry droppings on diesel contamination resulted in change of intensity of some physicochemical properties such as pH, EC, macro and micro nutrients, enzymes level, microbial population and soil fertility indices. The results indicated that macro and micro nutrients level can be increased via composting method. This bio remediated soil is suitable for crop cultivation.